Factor contributing to Occupational Hazards among Health Workers in Mbale Regional Referral Hospital Mbale District. A Cross-sectional Study. - Nambuya, Grace; Were , Amiri (Student’s Journal of Health Research Africa, 2022)
Background: Health workers are exposed to many occupational hazards because of the kind of environment they work in. Occupational health and safety is an important issue because of the high rates of associated morbidity and mortality of exposed workers ( Ajayi AD, Garba SN, Abdul AJ, Mfuh 2006). The purpose of this study is to determine factors contributing to occupational hazards among health workers in Mbale Regional Referral Hospital. Methodology: The study uses a descriptive cross-sectional study design to yield results from the study in a relatively short period. This design is preferred because it involves the use of varied methodologies and data sources that will help to ensure more accuracy and stronger research outcomes by triangulating data from different methods. Results: According to individual factors, 46% noted that it was due to multi-tasking. Health facility-related factors leading to occupational hazards, the highest number 45% said that they did not always use protective gear. By environmental factors, the highest number 45% noted that it was due to pressure at work, and the pressure was caused by many patients at the facility. Conclusion: Multi-tasking, inadequate training, and pressure at work can lead to occupational hazards among health workers. Recommendations: Provision of adequate medical supplies to the hospital and provision of continuing medical education is key to reducing occupational hazards.